2022
DOI: 10.1007/s00521-022-07424-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning applications for COVID-19 outbreak management

Abstract: Recently, the COVID-19 epidemic has resulted in millions of deaths and has impacted practically every area of human life. Several machine learning (ML) approaches are employed in the medical field in many applications, including detecting and monitoring patients, notably in COVID-19 management. Different medical imaging systems, such as computed tomography (CT) and X-ray, offer ML an excellent platform for combating the pandemic. Because of this need, a significant quantity of study has been carried out; thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 138 publications
0
20
0
Order By: Relevance
“…To date, a wide range of DL models have been proposed to solve various problems (both guided learning and individual learning) [ 34 ]. Most of them are used for purposes such as image ordering, object recognition, and general language preparation, and the output layer consists of several nodes that determine the probability of each label.…”
Section: System Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a wide range of DL models have been proposed to solve various problems (both guided learning and individual learning) [ 34 ]. Most of them are used for purposes such as image ordering, object recognition, and general language preparation, and the output layer consists of several nodes that determine the probability of each label.…”
Section: System Methodologymentioning
confidence: 99%
“…According to [ 3 ], the authors utilized a combined CNN-LTSM model using a time-series dataset to predict the confirmed cases of COVID-19 [ 33 ]. The CNN-LTSM encoder-decoder technique helps significantly boost prediction performance [ 34 ]. The study in [ 4 ] proposed an RNN-based model which was the modified version of LSTM to predict the mortality ratio, infected patients, and recovered positive patients.…”
Section: Literature Surveymentioning
confidence: 99%
“…Many works from the state of the art are using deep learning to solve biomedical problems [23] , [24] , [25] , [26] , [27] . Recently works in literature have been applying deep learning as tertiary analysis such as viral prediction, viral host prediction, and viral segments prediction [17] , [12] , [18] , [20] , [13] , [28] , [19] , [29] , [14] , [30] , [31] , [32] , [15] , [16] , [33] , [34] , [35] , [36] .…”
Section: Related Workmentioning
confidence: 99%
“…When ultrasound imaging detects patient lesions, the smoothness of the organ surface and the location of the lesions can be checked, and real-time image inspection can be performed [15]. Deep learning technology has achieved success in the construction of large-scale image datasets for natural image recognition [16]. The bilinear convolutional neural network (BCNN) is able to classify images very well.…”
Section: Introductionmentioning
confidence: 99%